Comparative financing analysis and political economy of noncommunicable diseases. (3rd August 2019) - Jakovljevic, Mihajlo; Jakab, Melitta; Gerdtham, Ulf; McDaid, David; Ogura, Seiritsu; Varavikova, Elena; Merrick, Joav; Adany, Roza; Okunade, Albert; Getzen, Thomas E.
Abstract: The pandemic of chronic non-communicable diseases (NCDs) poses substantial challenges to the health financing sustainability in high-income and low/middle income countries (LMICs). The aim of this review is to identify the bottle neck inefficiencies in NCDs attributable spending and propose sustainable health financing solutions. The World Health Organization (WHO) introduced the "best buy" concept to scale up the core intervention package against NCDs targeted for LMICs. Population- and individual-based NCD best buy interventions are projected at US$170 billion over 2011–2025. Appropriately designed health financing arrangements can be powerful enablers to scale up the NCD best buys. Rapidly developing emerging nations dominate the landscape of LMICs. Their capability and willingness to invest resources for eradicating NCDs could strengthen WHO outreach efforts in Asia, Africa, and Latin America, much beyond current capacities. There has been a declining trend in international donor aid intended to cope with NCDs over the past decade. There is also a serious misalignment of these resources with the actual needs of recipient countries. Globally, the momentum towards the financing of intersectoral actions is growing, and this presents a cost-effective solution. A budget discrepancy of 10:1 in WHO and multilateral agencies remains in donor aid in favour of communicable diseases compared to NCDs. LMICs are likely to remain a bottleneck of NCDs imposed financing sustainability challenge in the long-run. Catastrophic household health expenditure from out of pocket spending on NCDs could plunge almost 150 million people into poverty worldwide. This epidemiological burden coupled with population ageing presents an exceptionally serious sustainability challenge, even among the richest countries which are members of the Organization for Economic Co-operation and Development (OECD). Strategic and political leadership of WHO and multilateral agencies would likely play essential roles in the struggle that has just begun.